The knowledge of students attending selected higher education institutions in Lublin on cervical cancer prevention - Mazur, Paulina; Kuśmierz, Magdalena; Kwiatkowska, Karolina; Sztaba, Gabriela; Rząca, Marcin Stanisław; Domżał-Drzewicka, Renata; Stanisławek, Andrzej (Journal of Education, Health and Sport, 2017)
Background: Cervical cancer constitutes one of the main global-scale oncological problems, also observed among Polish women. Young women and men should be aware of risk factors and early symptoms, and understand and accept the significance of participation in the secondary prevention of this type of neoplasm. Objective: To assess the level of knowledge of students attending selected higher education institutions in Lublin on cervical cancer. Material and methods: Questionnaire surveys were carried out on a group of 360 students of the Medical University of Lublin (UM) (n=119), the University of Life Sciences in Lublin (UP) (n=122) and the Lublin University of Technology (PL) (n=119). Sample selection was purposive. The respondents’ average age was 21.8±1.4 years. A self-designed questionnaire was the research tool. Results: Sexual contact with a person infected with HPV was indicated as a cervical cancer risk factor by 97% of UM students, 74% of UP students and 79% of PL students. PL students less often than UM and UP students were aware of the negative effects of cervical cancer risk factors. The highest level of knowledge on cervical cancer was presented by UM students, a medium level of knowledge – by UP students, and the lowest – by PL students. Students of technical and life sciences universities diminished the harmfulness of risk factors or considered them neutral more often than UM students. PL students the least often accurately selected the symptoms of cervical cancer from the prepared list. Only 41% of UP students and 33% of PL students were able to accurately identify the age ranges of women covered by the prevention programme for the early detection of cervical cancer. Conclusions: The highest level of knowledge on prevention was presented by Medical University students, and the lowest by the students of the University of Technology. The higher education institution’s profile is a statistically significant determinant of the students’ level of knowledge. Especially female students of life sciences and technical universities require education on regular cervical cytology tests.